Treatment of Allergic Rhinitis and Asthma in Primary Care: Dispensations Do Not Align with Prescriptions - Belhassen M; Bérard M; Devouassoux G; Dalon F; Bousquet J; Van Ganse E (Journal of Asthma and Allergy, 2022)
Manon Belhassen,1 Marjorie Bérard,1 Gilles Devouassoux,2 Faustine Dalon,1 Jean Bousquet,3,4 Eric Van Ganse1,2,5 1Pelyon, Pharmacoepidemiology Lyon, Lyon, France; 2Respiratory Medicine, Croix Rousse Hospital, Lyon, France; 3MACVIA-France, Fondation Partenariale FMC VIA-LR, Montpellier, France; 4INSERM U 1168, VIMA, Ageing and Chronic Diseases Epidemiological and Public Health Approaches, Villejuif, France; 5Research on Health Care Performance RESHAPE, INSERM U1290, University Claude Bernard Lyon 1, Lyon, FranceCorrespondence: Eric Van Ganse, Respiratory Medicine, Croix Rousse Hospital, Lyon, France, Tel +33 472  071  730, Email eric.van-ganse@chu-lyon.frBackground: Appropriate use of effective treatments is required for satisfactory control of allergic symptoms. Coherent medical care -regular prescribing by the same Health Care Professionals- is a preliminary need.Objective: We investigated the numbers of distinct prescribers, the regularity of medical visits, and the agreement between prescriptions and associated dispensations in individual patients with perennial allergic rhinitis (PAR) and asthma.Methods: In primary care electronic health records (EHRs), a cohort of patients with PAR and asthma was identified. Individual EHRs were linked to corresponding claims recording all dispensations. Prescribing patterns were analyzed for the major treatment classes, and the dispensations linked to individual prescriptions were retrieved to compute the proportions of days covered (PDCs) for asthma and PAR therapy.Results: A total of 3654 patients were included, with 62% being female (mean age, 46.1 years). At inclusion, asthma control was not optimal in 51% of the patients and 48% had received oral corticosteroids. The mean interval between successive prescriptions varied between 93 (leukotriene receptor antagonists, LTRAs) and 103 (inhaled corticosteroids, ICS) days, and 97 (antihistamines, AHs) and 103 days (nasal corticosteroids, NCS). On average, individual prescriptions lead to 1.2, 1.5, 1.7 and 1.8 dispensations of ICS, ICS/Long-Acting Beta-Agonist (LABA) fixed-dose combinations, LABAs, and LTRAs, respectively, and to 1.3 and 1.6 dispensations of NCS and AHs, respectively. PDCs then varied between 37.8% for ICS and 58.6% for LTRAs, and between 39.7% for NCS and 50.4% for AHs. Care was nonetheless coherent, with > 90% of all dispensations related to prescriptions issued by single General Practitioners (GPs).Conclusion: Despite regular healthcare visits and medication prescriptions, allergic patients only partly and selectively refilled their treatments, preferring the less effective therapy, in a context of poor control of asthma symptoms.Keywords: asthma, rhinitis, care, control, therapy, adherence, misuse